Gender mainstreaming in European Union development policy toward Latin America : transforming gender relations or confirming hierarchies - Debusscher, Petra (2012)
Examines gender mainstreaming in the Latin American development policy of the EU through quantitative and qualitative analysis of policy programming document. States that the transformative potential of this approach has been neglected. Notes that the exclusion of women's organisations from the drafting process and the gap between civil society's and EUs framings of gender (in)equality in LA may be responsible for this situation.